2020
DOI: 10.1183/16000617.0060-2020
|View full text |Cite
|
Sign up to set email alerts
|

Breathing fresh air into respiratory research with single-cell RNA sequencing

Abstract: The complex cellular heterogeneity of the lung poses a unique challenge to researchers in the field. While the use of bulk RNA sequencing has become a ubiquitous technology in systems biology, the technique necessarily averages out individual contributions to the overall transcriptional landscape of a tissue. Single-cell RNA sequencing (scRNA-seq) provides a robust, unbiased survey of the transcriptome comparable to bulk RNA sequencing while preserving information on cellular heterogeneity. In just a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 155 publications
(179 reference statements)
0
8
0
1
Order By: Relevance
“…The process requires careful testing of how changing conditions affects the quality of sample generated [52]. While aggressive or prolonged digestion protocols may lead to cell death or fragmentation [53], gentle dissociation protocols may lead to greater capture of easily dissociated cells, which might be a challenge in the lung diseases characterized by altered matrix structures [54]. We did observe an absence in type II epithelial cell capture prior to selection, suggesting epithelial cell viability may contribute their diminished detection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The process requires careful testing of how changing conditions affects the quality of sample generated [52]. While aggressive or prolonged digestion protocols may lead to cell death or fragmentation [53], gentle dissociation protocols may lead to greater capture of easily dissociated cells, which might be a challenge in the lung diseases characterized by altered matrix structures [54]. We did observe an absence in type II epithelial cell capture prior to selection, suggesting epithelial cell viability may contribute their diminished detection.…”
Section: Discussionmentioning
confidence: 99%
“…We did observe an absence in type II epithelial cell capture prior to selection, suggesting epithelial cell viability may contribute their diminished detection. In fact in a review of published datasets, Alexander et al, have reported that in normal lung tissue cell types, such as broad, flat, sail-like alveolar type I (AT1) cells and matrix-embedded fibroblasts, are difficult to dissociate and liberate and as such are relatively underrepresented when compared with cuboidal alveolar type II (AT2) cells and alveolar macrophages [53]. Low capture/detection of epithelial cells in the fetal and newborn human lung may be attributed to the developmental age of the studied samples, cellular stress encountered due to the dissociation protocols or difficulty in capture of these cells with the Chromium 10X protocol.…”
Section: Discussionmentioning
confidence: 99%
“…La secuenciación de RNA en una sola célula (scRNA-seq) proporciona un examen robusto e imparcial del transcriptoma que es comparable a la secuenciación masiva de RNA, al tiempo que preserva la información sobre la heterogeneidad celular. Esta técnica ha permitido avances impresionantes, como el descubrimiento del ionocito pulmonar y de la población de macrófagos profibróticos en la fibrosis pulmonar [26]. Los datos surgidos del análisis de scRNA-seq han aportado nuevos conocimientos sobre la disfunción de las células epiteliales progenitoras alveolares de tipo II y la diversidad de las células mesenquimales dentro del pulmón fibrótico [27].…”
Section: Causas Claras Y Mecanismos Aún No Resueltos De La Silicosisunclassified
“…Lung tissues, sera, peripheral blood leukocytes, and bronchoalveolar lavage fluids (BALFs) collected from silicotic patients or animals and in vitro models (such as silica- or TGF- β 1-induced macrophages or fibroblasts) have been applied in omics approaches to screen diagnostic biomarkers, explore new mechanisms, and reveal potential therapeutic targets [ 21 25 ]. Single-cell RNA sequencing (scRNA-seq) provides a robust and unbiased survey of the transcriptome that is comparable to bulk RNA sequencing, while preserving cellular heterogeneity information has contributed to impressive advancements, including the discoveries of the pulmonary ionocyte and the profibrotic macrophage population in pulmonary fibrosis [ 26 ]. Emerging data from scRNA-seq analysis have provided novel insights on the dysfunction of alveolar type II progenitor epithelial cells and the diversity of mesenchymal cells within the fibrotic lung [ 27 ].…”
Section: Clear Causes and Unresolved Mechanisms Of Silicosismentioning
confidence: 99%